(untitled) (Training and Practice : Journal of Educational Sciences, 2008)
The paper presents a quite special initiative, on which a group of researchers returned back a detailed report about the research’s results in a form of “feedback” note-books, to those schools who participated in a research exploring the learner’s learning caracteristics. The researchers believed that the exploration, interpretation of children’s learning caracteristics and teaching reccomendations would be a helpful support for teacher in realizing an instruction which respect the individual specifics, but also for children in improving self-knowledge. The paper briefly introduces the mentioned research, the conceptional background, the interpretation of learning caracteristics and finally gives particulars about the contents of so-called “feed/back” note-books.